Roles and Clinical Significances of ATF6, EMC6, and APAF1 in Prognosis of Pancreatic Cancer - Xiao, Wang; Cao, Rong-Chang; Yang, Wan-Jun; Tan, Jie-Hui; Liu, Ruo-Qi; Kan, He-Ping; Zhou, Lei; Zhang, Na; Chen, Zhi-Ye; Chen, Xue-Mei; Xu, Jia; Zhang, Guo-Wei; et al. (Frontiers in Genetics, 2022)
Background: Pancreatic cancer (PC) is prevalent among malignant tumors with poor prognosis and lack efficient therapeutic strategies. Endoplasmic reticulum (ER) stress and apoptosis are associated with chronic inflammation and cancer progression. However, the prognostic value of ER stress-related and apoptosis-related genes in PC remains to be further elucidated. Our study aimed at confirming the prognostic values of the ER stress-related genes, ATF6, EMC6, XBP1, and CHOP and the apoptosis-related gene, APAF1, in PC patients. Methods: Gene Expression Profiling Interactive Analysis (GEPIA2) was used to evaluate prognosis value of ATF6, EMC6, XBP1, CHOP and APAF1 in PC. Clinical data from 69 PC patients were retrospectively analyzed. Immunohistochemistry, western blotting, and qRT-PCR were used for the assessment of gene or protein expression. The Cell counting kit-8 (CCK-8) and the Transwell invasion assays were respectively used for the assessment of PC cells’ proliferative and invasive abilities. The prognostic values of ATF6, XBP1, CHOP, EMC6 and APAF1 in PC patients were evaluated using Kaplan-Meier and Cox regression analyses. Results: XBP1 and CHOP expression were not associated with PC recurrence-free survival (RFS), overall survival (OS) and disease-specific survival (DSS). ATF6 upregulation and EMC6 and APAF1 downregulations significantly correlated with the poor RFS, OS and DSS of PC patients. ATF6 promoted PC cells proliferation and invasion, while EMC6 and APAF1 inhibited these events. Conclusion: ATF6 upregulation and EMC6 and APAF1 downregulations may be valid indicators of PC patients’ poor prognosis. Moreover, ATF6, EMC6 and APAF1 may constitute potential therapeutic targets in PC patients.